Implementasi CTL Dalam Pembelajaran Ismul Isyarah Untuk Meningkatkan Maharah al-Kalam Siswa Kelas X F MA Al-Mukmin Ngruki Sukoharjo - Diva Putri Anisa (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2025)
This study was motivated by students’ low ability in mastering ismul isyarah and their difficulties in developing speaking skills (maharah al-kalam) in Arabic learning. The objectives of this study are to describe the implementation of CTL approach, to analyze its outcomes, and to identify its strengths and weaknesses in teaching ismul isyarah. This research employed a qualitative descriptive method. Data were collected through classroom observation, interviews, and documentation in Class X F of MA Al-Mukmin Ngruki. The findings revealed that in the first meeting, nine students did not achieve the minimum passing grade (KKM), scoring between 45–63. However, in the second meeting, all students successfully exceeded the KKM, with scores ranging from 70–98. The implementation of CTL significantly improved students’ speaking skills. They became more active, confident, and able to use ismul isyarah correctly in real-life contexts. The strengths of CTL include creating active learning, making grammatical rules more practical, encouraging collaboration, and increasing students’ self-confidence. Its weaknesses are that CTL requires more flexible time, well-prepared teachers, and sufficient learning media. Therefore, CTL can be recommended as an effective approach for communicative Arabic language teaching.